Production of Bioactive Recombinant Reteplase by Virus-Based Transient Expression System in Nicotiana benthamiana - Ma, Ting; Li, Zhiying; Wang, Sheng (Frontiers in Plant Science, 2019)
To explore a cost-effective alternative method to produce the recombinant thrombolytic drug Reteplase (rPA), a plant viral amplicon-based gene expression system was employed to transiently express bioactive Strep II-tagged recombinant rPA in Nicotiana benthamiana leaves using agroinfiltration. Several gene expression cassettes were designed, synthesized in vitro, and then cloned into Tobacco mosaic virus (TMV) RNA-based overexpression vector (TRBO). Codon optimization, subcellular targeting, and the effect of attached Strep-tag II were assessed to identify conditions that maximized expression levels of the recombinant rPA in tobacco leaves. We found that codon optimized rPA with N-terminal Strep-tag II that was targeted to the endoplasmic reticulum (ER) provided the highest amount of biologically active protein; i.e. up to ~50 mg from per kilogram fresh weight leaf biomass in less than one week. Furthermore, the recombinant rPA was conveniently purified from inoculated leaf extracts by a one-step purification procedure via the Strep-tag II. The plant-made rPA was glycosylated with molecular mass of ~45.0 kDa and its in vitro fibrinolysis activity was equivalent to the commercial available rPA. These results indicate that the plant viral amplicon-based system offers a simple and highly effective approach for cost-effective large-scale production of recombinant rPA.